The effect of different soil amendment agents on physical and chemical properties of saline soils - MA Fuyang; CAO Weiwei; PENG Hao; YAO Rongjiang; WANG Xiuping; LIU Guangming; ZHANG Wentai (Guan'gai paishui xuebao)
【Objective】 Soil conditioners are commonly used to improve quality and productivity of saline soils. This paper experimentally compares the effects of different soil conditioners on the physical and chemical properties of saline soils. 【Method】 The experiment was conducted in pots to simulate a rice-oilseed rape rotational cropping system. The soil was amended with calcium superphosphate at rates of 750 kg/hm2 (G1) and 1 500 kg/hm2 (G2); hydrolyzed poly (maleic anhydride) at rates of 900 kg/hm2 (J1), 1 200 kg/hm2 (J2) and 1 500 kg/hm2 (J3); and Bacillus megaterium at rates of 40 kg/hm2 (W1), 60 kg/hm2 (W2), and 80 kg/hm2 (W3). The control treatment (CK) was conventional fertilization without soil amendment. In each treatment, we measured physical soil properties and electrical conductivity of soil solution.【Result】Compared to CK, J2 increased soil total porosity, maximum water holding capacity, field water holding capacity, and capillary water holding capacity by 12.49%, 13.60%, 13.63% and 12.41%, respectively, while reducing electrical conductivity of the soil solution by 64.73%. W2 improved total soil porosity, maximum water holding capacity, field water holding capacity, and capillary water holding capacity by 8.59%, 9.57%, 9.01%, and 9.79%, respectively, while reducing electrical conductivity of the soil solution by 55.66%. W1 reduced soil bulk density by 4.20%, enhanced maximum water holding capacity, field water holding capacity, capillary water holding capacity and soil organic matter by 6.58%, 9.02%, 9.69% and 25.82%, respectively, while reducing electrical conductivity of soil solution by 8.97%.【Conclusion】Principal component analysis ranked the conditioners and their application rates in terms of their efficacy the following order: 1 200 kg/hm2 of hydrolyzed poly (maleic anhydride) > 60 kg/hm2 of Bacillus megaterium > 40 kg/hm2 of Bacillus megaterium. These findings provide a guidance for practical application of soil amendment agents to improve properties and productivity of saline soils in the studied regions.